Exploring the electrocatalytic application of two-dimensional samarium molybdate (γ-Sm3(MoO4)3) nanoplatelets for the selective sensing of the organophosphate insecticide oxyparathion. (27th February 2020) - Kumar, Jeyaraj Vinoth; Mutharani, Bhuvanenthiran; Chen, Shen-Ming; Rajakumaran, Ramachandran; Nagarajan, Erumaipatty Rajagounder
Abstract : Novel samarium molybdate structures were synthesized through a simple ultrasonic method and exhibited excellent electrocatalytic activity toward oxyparathion. Abstract : The exploration of novel and proficient materials through simple, large-scale and green synthesis routes for the detection of precise levels of organophosphate insecticides in real physical systems of soil and water is a predominant concern of researchers. In light of this, we introduced a sensitive and eminently selective electrochemical sensor probe for oxyparathion (OP) based on sonochemically designed 2D samarium molybdate nanoplatelets (γ-Sm3 (MoO4 )3 ; SmM NPs). The sonochemically synthesized SmM NP catalyst was systematically investigated with respect to the crystal structure, textural morphologies, and physicochemical characteristics by XRD, Raman, FE-SEM, HR-TEM, and XPS analysis. The fabricated electrode was employed for detection and determination through different voltammetric techniques. The SmM NP fashioned screen-printed carbon electrode (SmM NPs/SPCE) demonstrated potentially superior electrocatalytic activity towards OP detection with a lower detection limit, widespread linear amplitude range and good sensitivity of 0.002 μM, 0.01–692 μM, and 0.54 μA μM −1 cm −2, correspondingly. Moreover, other interfering materials, such as inorganic species, biological compounds and nitro-group-containing OPPTs and drugs, have no influence on the detection of OP. Besides, SmM NPs/SPCE has also been utilized for OP detection in soil and actual groundwater samples and displayed excellent sensing abilities.